2011
DOI: 10.3748/wjg.v17.i45.5028
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide induces mucosal healing in Crohn's disease: Case report

Abstract: Crohn's disease is a chronic inflammatory disorder of the gastrointestinal tract that is defined by relapsing and remitting episodes. Tumor necrosis factor alpha (TNF-α) appears to play a central role in the pathophysiology of the disease. Standard therapies for inflammatory bowel disease fail to induce remission in about 30% of patients. Biological therapies have been associated with an increased incidence of infections, especially infection by Mycobacterium tuberculosis (Mtb). Thalidomide is an oral immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…While it is undeniable that the two conditions could coexist in countries with a high TB prevalence, one hypothesis suggests that Mycobacterium avium subspecies might be a cause of CD[ 22 ]. In 2011, a successful use of thalidomide under such circumstances in patients with CD and also tuberculosis infection was also reported[ 9 ]. In fact, thalidomide has been shown to be effective as an adjuvant treatment for intractable intracranial tuberculosis and central nervous system tuberculosis infection that did not respond to standard medical and surgical therapy[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is undeniable that the two conditions could coexist in countries with a high TB prevalence, one hypothesis suggests that Mycobacterium avium subspecies might be a cause of CD[ 22 ]. In 2011, a successful use of thalidomide under such circumstances in patients with CD and also tuberculosis infection was also reported[ 9 ]. In fact, thalidomide has been shown to be effective as an adjuvant treatment for intractable intracranial tuberculosis and central nervous system tuberculosis infection that did not respond to standard medical and surgical therapy[ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, we reported in our pilot study our experience that three pediatric patients with CD concomitant with tuberculosis achieved clinical remission after six months of thalidomide treatment[ 8 ]. Similarly, a later case report presented an adult patient with CD and pulmonary TB who was steroid-dependent and unresponsive to infliximab, but the patient exhibited an excellent response to thalidomide treatment[ 9 ]. In the present study, we enrolled 10 pediatric-onset patients who had symptoms and evidence suggestive of CD and tuberculosis in attempt to evaluate the efficacy of thalidomide in clinical remission of these cases in a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] MH in IBD could be achieved by several drugs, such as AZA, biological agents, corticosteroids, and thalidomide. [ 29 31 ] Scribano et al [ 32 ] reported the efficacy of thalidomide in 3 patients with moderate-to-severe CD who failed to biological anti-TNF agents, all the 3 patients at a low dose of thalidomide (50–150 mg/kg) for 9 to 36 months achieved clinical remission and MH. In our case, the postoperative recurrence patient achieved MH at a low dose of thalidomide (50–100 mg/kg) for 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…Restricting TNF overexpression in myeloid cells or T lymphocytes suffices for the induction of intestinal pathology, indicating the pathogenic potential of TNF derived from innate or adaptive effectors. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%